1975
DOI: 10.1126/science.49927
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of type C Virions from a Normal Human Fibroblast Strain

Abstract: Type C virions were spontaneously released from cultures of a diploid human cell strain. The varions have properties of known type C RNA tumor viruses and share antigenic determinants with the major interspecies-specific antigen (p30) of simian sarcoma virus. Antiserum to reverse transcriptase of gibbon ape leukemia virus inhibits the reverse transcriptase of the putative human virions and that of simian sarcoma virus, but has no effect on the corresponding enzymes of avian or murine RNA tumor viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

1977
1977
1981
1981

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 19 publications
1
55
0
Order By: Relevance
“…The growth and purification of HEL-12 virus from culture fluids of virusproducing cells has been described (Panem et al, 1975). SiSV(SSAV) (Bergholz et al, 1977) produced by marmoset fibroblasts (HF) was grown and purified according to well-established protocols in a different building to avoid any cross-contamination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth and purification of HEL-12 virus from culture fluids of virusproducing cells has been described (Panem et al, 1975). SiSV(SSAV) (Bergholz et al, 1977) produced by marmoset fibroblasts (HF) was grown and purified according to well-established protocols in a different building to avoid any cross-contamination.…”
Section: Methodsmentioning
confidence: 99%
“…Comparative studies have demonstrated that these virus isolates are related to both BaEV and SiSV/GALV Teich et al, 1975;Chan et al, 1976;Panem et al, 1975). One of these isolates, HEL-12 virus, was 0022-1317/81/0000-4399 $02.00 ;~ 1981 SGM spontaneously released from a strain of normal human embryonic lung fibroblasts (Panem et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sci. USA 74 (1977) viruses highly related to mem'bers of this virus group (25)(26)(27)(28)(29)(30) and, more recently, suggestive evidence for antibodies to this virus group in human sera (19,39,40). However, proviral sequences related to the simian sarcoma virus/gibbon ape leukemia virus group have not as yet been reported (14).…”
mentioning
confidence: 99%
“…Recently, nucleic acids and proteins related to the two known primate type-C virus groups-the simian sarcoma virus/gibbon ape leukemia virus group and the baboon endogenous virus group-have been reported in fresh human tissues (5-8, 11-14, 16, 18-23) (20)(21)(22)(23) have been contested (24). Although clearly a rare event, isolation of a replicating virus from human tissues related to one or both of these primate type-C viruses has also been reported (25)(26)(27)(28)(29)(30). Until The objective of experiments reported here was to examine DNA from human tissues for sequences related to RNA of MuLVR in more detail and with more carefully prepared cDNA probes.…”
mentioning
confidence: 99%